Analysis of Ce3+ luminescence quenching in solid solutions between Y3Al5O12 and Y3Ga5O12 by temperature dependence of photoconductivity measurement - Ueda, Jumpei; Tanabe, Setsuhisa; Nakanishi, Takayuki (Journal of applied physics, 2011)
Photocurrent excitation spectra were measured to investigate the quenching in the garnet solid solutions. Intense photocurrent excitation bands attributed to the lowest 5d1 and the second lowest 5d2 levels were observed in the Ce-doped Y3Al2Ga3O12 (Ce:YAGG) and Y3Ga5O12 (Ce:YGG). Based on the results of temperature dependence of photoconductivity, the 5d1 and 5d2 levels in the Ce:YAGG are found to be located below and within the conduction band, respectively, while both levels in the Ce:YGG are found to be located within its conduction band located at lower energy levels. In addition, the threshold of photoionization from the 4f level of Ce3+ to the conduction band in the Ce:YAGG and Ce:YGG were estimated to be 3.2, and 2.8 eV, respectively. We conclude that the main quenching process in the Ce:YAGG is caused by the thermally stimulated ionization process with activation energy of 90 meV from the 5d1 to the conduction band, and that in the Ce:YGG is caused by the direct ionization process from the 5d levels to the conduction band.